Analisis Penerapan Pembelajaran Berbasis Inkuiri dalam Pembelajaran IPA di Sekolah Dasar - Herdianti, Sri; Istiqomah, Alya Syafia; Saleha, Aisha Nur; Permata, Saidah Nur; Perdiansyah, Ferry (IJPSE Indonesian Journal of Primary Science Education, 2026)
This study aims to describe the implementation of inquiry-based learning in science subjects in elementary schools deeply. The method used was qualitative research with a descriptive approach. Data were collected through observations of student activities, interviews with teachers regarding students' understanding of student characteristics, and documentation of learning tools. The results of the study indicate that science learning at SDN Sukasari 5 is implemented through an inquiry method integrated with project-based activities. The implementation of this model encourages students to be actively involved through observation, group work, and direct investigation, which helps improve their science process skills and academic achievement. Despite of obstacles such as time constraints and differences in student activity levels, the inquiry model has proven effective in creating student-centered learning and instilling scientific attitudes such as curiosity and cooperation.